Soil fertility and agriculture yield with the application of organomineral or mineral fertilizers in solid and fluid forms - Correa, Juliano Corulli; Rebellatto, Agostinho; Grohskopf, Marco Andre [UNESP]; Cassol, Paulo Cezar; Hentz, Paulo; Rigo, Amanda Zolet (Empresa Brasil Pesq Agropec, 2018)
The objective of this work was to evaluate the effects of organomineral and mineral fertilizers, in their solid and fluid forms, on soils with variable charges with high fertility built up from nitrogen, phosphorus, and potassium contents in the soil and plant, as well as on corn (Zea mays) and black oat (Avena strigosa) yield. The treatments consisted of one control and four fertilizers - two organomineral and two mineral - in solid (SO, solid organomineral; and SM, solid mineral) and fluid (FO, fluid organomineral; and FM, fluid mineral) forms applied in Rhodic Kandiudox and Distrochrept soils with no-tillage. The use of organomineral or mineral fertilizers in fluid and solid forms increases total N content in the soil, maintains exchangeable K content in both soils, and may enhance available P content to the depth of 0.6 m in Distrochrept. These factors allowed significantly increasing corn yield, regardless of the fertilizer, and establishing greater residual effect for fluid organomineral fertilizer in the winter black oat yield, even in soils with high fertility.
Keywords: Avena strigosa; Zea mays; crop system fertilization; liquid pig slurry; no-tillage; poultry litters